Eligibility criteria in NIH-funded clinical trials: Can adults with intellectual disability get in?. Issue 4 (October 2022) - McDonald, Katherine E.; Schwartz, Ariel E.; Sabatello, Maya
Abstract: Background: Although scientific breakthroughs can promote health equity, there is concern that adults with intellectual disability, a health disparities population, may be excluded from clinical trials. Objective: To determine the extent to which adults with intellectual disability are subject to exclusion from National Institutes of Health (NIH)-funded clinical trials. Methods: We studied recent NIH-funded Phase 2/3, 3, and 4 clinical trials of United States-based working-age adults (>18 < 55 years of age) listed in ClinicalTrials.gov. We coded eligibility criteria for inclusion, direct exclusion, and indirect exclusion of adults with intellectual disability. Results: We rarely identified studies that directly include adults with intellectual disability. Most studies (74.6%) had eligibility criteria that directly and/or indirectly exclude adults with intellectual disability. Approximately one-third of studies had direct exclusion criteria based on cognitive impairment or diagnosis of intellectual disability. Nearly 65% of studies indirectly excluded adults with intellectual disability based on factors likely associated with intellectual disability (e.g., functional capacity, inability to read/write, and/or research staff discretion). Conclusions: We found less exclusion based on diagnosis of intellectual disability than anticipated. Nonetheless, about three-fourths of studies had eligibility criteria which would likely lead to the direct and/or indirect exclusion of adults with intellectual disability. Our findings suggest substantial cause for concern that adults with intellectual disability experience widespread exclusion from NIH-funded clinical trials—exclusion that may lack appropriate justification and assessment. Consequently, this group is denied equal access to the potential benefits of scientific discovery. We provide recommendations for approaches to include adults with intellectual disability. Highlights: Adults with intellectual disability need to participate in research to derive associated health benefits. 74.6% of NIH-funded clinical trials had eligibility criteria that could exclude adults with intellectual disability. About one-third of studies directly excluded adults with intellectual disability. 64.5% of studies may have indirectly excluded adults with intellectual disability. Accommodations and attention to eligibility criteria may promote inclusion in clinical trials and health equity.